2009
DOI: 10.1002/hep.22729
|View full text |Cite
|
Sign up to set email alerts
|

Early gene expression profiles of patients with chronic hepatitis C treated with pegylated interferon-alfa and ribavirin

Abstract: Responsiveness to hepatitis C virus (HCV) therapy depends on viral and host factors. Our aim was to assess sustained virologic response (SVR)-associated early gene expression in patients with HCV receiving pegylated interferon-alpha2a (PEG-IFN-␣2a) or PEG-IFN␣2b and ribavirin with the duration based on genotypes. Blood samples were collected into PAXgene tubes prior to treatment as well as 1, 7, 28, and 56 days after treatment. From the peripheral blood cells, total RNA was extracted, quantified, and used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
3
33
1
1
Order By: Relevance
“…This might have some implications regarding the role of pretherapeutic lower level of IRF-2 in predicting sustained virological response (SVR) in previously treated CHC subjects. 26 Our data are in contrast to the finding that IFN-α gene expression is downregulated in the liver but upregulated in PBMC of CHC subjects. 13 However, our data are in accordance with a recent report where IRF-2 expression was shown to be upregulated with enhanced IRF-2 oncogenic protein expression in CD19-positive blood B cells obtained from CHC subjects.…”
Section: S T a T --C O N T R O L S T A T -1 -A L T ( Hcontrasting
confidence: 99%
“…This might have some implications regarding the role of pretherapeutic lower level of IRF-2 in predicting sustained virological response (SVR) in previously treated CHC subjects. 26 Our data are in contrast to the finding that IFN-α gene expression is downregulated in the liver but upregulated in PBMC of CHC subjects. 13 However, our data are in accordance with a recent report where IRF-2 expression was shown to be upregulated with enhanced IRF-2 oncogenic protein expression in CD19-positive blood B cells obtained from CHC subjects.…”
Section: S T a T --C O N T R O L S T A T -1 -A L T ( Hcontrasting
confidence: 99%
“…Other groups described that gene expression in PBMCs was predictive of treatment outcome (10,36). One group demonstrated that the expression of STAT6 and SOCS1 was predictive of the SVR in pretreatment samples (36).…”
Section: Discussionmentioning
confidence: 99%
“…One group demonstrated that the expression of STAT6 and SOCS1 was predictive of the SVR in pretreatment samples (36). These genes were not included in our assay.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that the development of non-invasive diagnostic biomarkers reliably differentiating chronic hepatitis C patients with and without steatosis will require an expanded list of the variables, or will have to resort to imaging technologies [33]. A potential source for additional candidate biomarkers would be gene expression or proteomic endpoints [34,35]. On the other hand, the insights derived from attempts to build these models further support the genotype-specific pathogenesis of hepatic steatosis in chronic hepatitis C infection.…”
Section: Discussionmentioning
confidence: 99%